Analisis Ketercapaian Persyaratan Kesehatan Lingkungan Industri di PT X - Fadlillah, Azmi Nur; Sukma Pawitra, Aditya (Media Kesehatan Masyarakat Indonesia, 2020)
Environmental health and industry have a relationship that will have an impact on worker health, work productivity, and other things that support the effectiveness and efficiency of the industry, some components such as soil, water, food, facilities, buildings, as well as vector and disease-carrying animals are aspects and requirements of industrial environmental health. This study aims to analyze the achievement of industrial environmental health requirements at PT X, referring to the Minister of Health Regulation No. 70 of 2016. This research was conducted from January to February 2020, using a descriptive qualitative design. Researchers explore information through interviews with informants and complete them with observation. The selected informants are employees in the K3LH Division, employees in the maintenance division, employees in the catering section, K3LH division managers, and catering section managers. The analysis technique used qualitative analysis on the assessment results according to the instruments used. This study found that the efforts for environmental health requirements at PT X had reached 89% of the total instruments analyzed. This happens because there are still some components that do not meet the requirements, such as WWTP, water-saving facilities, lactation facilities, smoking facilities, facilities for the disabled, and buildings that are densely packed with insects. The recommendation given is to improve and add several facilities related to environmental health requirements that are not yet available and then periodically reassess.